Endogenous Growth, Backstop Technology Adoption and Optimal Jumps - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
We study a two-phase endogenous growth model in which the adoption of a backstop technology (e.g. solar) yields a sustained supply of essential energy inputs previously obtained from exhaustible resources (e.g. oil). Growth is knowledge-driven and the optimal timing of technology switching is determined by welfare maximization. The optimal path exhibits discrete jumps in endogenous variables: technology switching implies sudden reductions in consumption and output, an increase in the growth rate, and instantaneous adjustments in saving rates. Due to the positive growth eect, it is optimal to implement the new technology when its current consumption bene.ts are substantially lower than those generated by old technologies.
Keywords: O33; Q32; Q43; 330; Backstop technology; Discrete jumps; Endogenous growth; Exhaustible resources; Optimal Control; Technologiewahl; Erschöpfbare Ressourcen; Kontrolltheorie; Endogenes Wachstumsmodell; Theorie